Socialist Register, 2001: Working classes and global realities - Lewchuk, Wayne (Labour / Le Travail, 2002)
The article reviews "Socialist Register, 2001: Working classes and global realities," edited by Leo Panitch and Colin Leys. The Register is published annually.
Keywords: Blue collar workers; Business And Economics--Labor And Industrial Relations; Capitalism; Employment; Globalization; History--History of North And South America; Labor; Labor unions; Social aspects; Social conditions; Workers; Working class; Working conditions